The role of technology transfer in enhancing agricultural productivity in Nigeria ("Journal "U". Economy. Management. Finance.", 2025)
The agricultural sector in Nigeria, a cornerstone of the country's economy, faces multiple challenges in enhancing productivity. This study focuses on the role of technology transfer in boosting agricultural productivity in Nigeria, emphasizing the importance of integrating modern technological innovations into farming practices. It examines the factors influencing technology adoption in rural areas, where agriculture remains predominantly traditional. The paper analyzes the potential of international trade and globalization to facilitate the transfer of advanced agricultural technologies to Nigeria, exploring the role of global partnerships, policy frameworks, and international cooperation. The study also considers how technology transfer can contribute to sustainable agricultural practices, improve the efficiency of resource use, and enhance food security. The research underscores the significance of aligning technological advancements with local agricultural conditions to maximize their effectiveness and benefit small scale farmers. By leveraging technology, Nigeria can overcome current productivity constraints and achieve long-term agricultural development goals
Keywords: technology transfer; agriculture; Nigeria; agricultural productivity; innovative technologies; international trade; globalization; rural areas; sustainable development; agribusiness; agricultural innovations; climate adaptation